2017
DOI: 10.1111/coa.12824
|View full text |Cite
|
Sign up to set email alerts
|

An undergraduate Otolaryngology curriculum comparison in the United Kingdom using a curriculum evaluation framework

Abstract: ObjectiveTo compare undergraduate otolaryngology curricula in the United Kingdom. To develop a tool which would allow undergraduate specialty curricula to be compared.DesignDevelopment of a curriculum evaluation framework (CEF) and survey.SettingUK medical schools.ParticipantsOtolaryngology curricula were requested from all 32 UK medical schools who award a primary medical qualification. Nineteen curricula were received and examined.Main outcome measuresThematic and content analysis of curriculum documents wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(17 citation statements)
references
References 18 publications
1
16
0
Order By: Relevance
“…However, despite its effectiveness, only a minority of UK medical schools currently use e-learning. 25…”
Section: Discussionmentioning
confidence: 99%
“…However, despite its effectiveness, only a minority of UK medical schools currently use e-learning. 25…”
Section: Discussionmentioning
confidence: 99%
“…In light of the minimal exposure to ENT within medical schools, 6 it is obvious why participants did not consider ENT as a career. The majority of participants felt they would consider ENT as a career now that they ‘know what ENT involves’.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of 26 medical schools showed that there were compulsory ENT placements and rotations for just 53 per cent of students, and 10 of the 26 medical schools included in the study did not offer an ENT attachment at all. 6 The average duration of an ENT attachment in medical schools varies from 7.5 to 13.4 days. 6,7 The short length of ENT attachments, or indeed the absence of them, is clearly inadequate, especially as more than 1 in 10 presentations to general practice involve ENT pathology.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In keeping with this change in paradigm, the concept of an associated shift to a national curriculum has been a move considered broadly within the UK medical education literature and otolaryngology to unify undergraduate experience [6][7] .…”
Section: Introductionmentioning
confidence: 99%